Winner-Takes-All or Co-Evolution among Platform Ecosystems: A Look at the Competitive and Symbiotic Actions of Complementors - Inoue, Yuki (Sustainability, 2019)
Technological platforms such as hardware or systems form platform ecosystems, which are communities orchestrated by platform providers, outside complementors such as software providers, and consumers. Previous studies have suggested that a winner-takes-all situation among platform ecosystems could be induced by interactions between complementors and consumers. However, our observation of the Japanese video game market over the last 30 years indicated that complementors (i.e., software providers) usually seek to avoid winner-takes-all situations and, instead, promote symbiotic situations. Using the Lotka–Volterra equations from biology as a reference, we developed a model to understand the competitive behavior of complementors among platform ecosystems. We used a 19-year (1996–2015) dataset on the Japanese video game market and confirmed that complementors took as many actions to create symbiotic situations as they took to create winner-takes-all situations, if not more. Our results show that such actions by complementors are influenced by several factors of platform ecosystems. This study also suggests that certain complementors that contribute to symbiotic co-existence within a platform ecosystem could emerge as keystone firms/companies. These complementors could contribute to the sustainability of platform-based markets and facilitate the co-existence of multiple platform ecosystems.